Two-Level Image Encryption Algorithm Based On Key-Image - Sridhar, V; Dyna, M (International Journal of Computer Sciences and Engineering, 2025)
In the contemporary world images play key role in information interchange. Medical, defence, space and various areas of domain make use of high scale images in several applications. Security becomes the main concern wherein the images are to be protected so that they cannot be seen by any advisory. This can be achieved by image encryption. There are various image encryption methods that are based on textual key and text data which are not efficient for high definition images. In this paper we propose a three step image encryption algorithm which uses another image as a key. In the first step, key image is scaled and tiled, in step2 encryption is achieved using grey-value substitution and in step-3 the output generated from step-2 is scrambled using Fibonacci transformation to add additional security. This multistep encryption provides high security for images. The performance of this algorithm is analyzed using different attack models which results in high security without any loss of input image